Mobile Communication and Local Information Flow: Evidence from Distracted Driving Laws - BROWN, NERISSA C.; STICE, HAN; WHITE, ROGER M. (Journal of Accounting Research, 2015)
ABSTRACT We examine the influence of mobile communication on local information flow and local investor activity using the enforcement of statewide distracted driving restrictions, which are exogenous events that constrain mobile communication while driving. By restricting mobile communication across a potentially sizable set of local individuals, these restrictions could inhibit local information flow and, in turn, the market activity of stocks headquartered in enforcement states. We first document a decline in Google search activity for local stocks when restrictions take effect, suggesting that constraints on mobile communication significantly affect individuals’ information search activity. We further find significant declines in local trading volume when restrictions are enforced. This drop in liquidity is (1) attenuated when laws provide substitutive means of mobile communication and (2) magnified when locals have long car commutes and when their daily commutes overlap with regular exchange hours. Moreover, trading volume suffers the most for local stocks with lower institutional ownership, less analyst coverage, and more intangible information. Additional analyses show lower intraday volume during local commute times when mobile connectivity is constrained. Together, our results suggest that local information and local investors matter in stock markets and that mobile communication is an important mechanism through which these elements operate to affect liquidity and price discovery.